The effects of resistance training on junior golfers' strength and on-course performance (International Journal of Golf Science, 2014)
The aim of this study was to examine the effect of resistance training on strength characteristics in junior golfers and observe the effect this has on golf performance. The study used a quasi-experimental design. Junior golfers (n = 30) were recruited and allocated to either an intervention (n = 20) or a control (n = 10) group for the 12-week study period. Assessments were conducted at baseline and 12 weeks. The primary outcome was change in strength over the intervention period. Effects on handicap were also assessed. No significant differences were found between groups at baseline for handicap or physical fitness variables. The intervention resulted in strength increases with all variables showing moderate to high effect sizes (d = 0.64-0.96). There was a moderate effect size for handicap (d = 0.42). Resistance-training programs can positively affect strength characteristics in junior golfers, which may influence golf performance. ABSTRACT FROM AUTHOR